Prevalence, clinico-epidemiological characteristics and risk factors of intestinal microsporidiosis in children with malignancy in the Institute of Pediatric, Kuala Lumpur, Malaysia - Ithnin, Nur Raihana (2013)
Intestinal microsporidiosis is an infection caused by Microsporidia, an obligate intracellular protozoan parasite that have a unique belt-like striped structure of the spore. The common species that infect human are Enterocytozoon bieneusi and Encephalitozoon spp. This infection common in immunocompromised individuals especially in HIV patients. Nonetheless, data from other immunocompromised individuals such as children, elderly, patients undergoing immunosuppressive therapy are still scanty. On the other hand, it had been widely reported in immunocompetent population currently. The prevalence of microsporidiosis varies and it depends on the use of diagnostic methods to detect the spore in the sample, the geographic distribution and the type of studied population. The aim of the study was to determine the prevalence of microsporidiosis in malignancy children population in Institute of Pediatric, Malaysia and to determine the possible risk factors that might be associated with microsporidiosis. In addition, the performance of Calcofluor White M2R (CFW) fluorescence staining compared with Modified Gram-chromotrope Kinyoun (MGCK) staining also will be determined. This cross sectional study was conducted from November 2009 until August 2010 in KK3 Oncology ward, Institute of Pediatrics, Hospital Kuala Lumpur. One hundred and six stool (n=106) samples from children with different types of malignancies were collected from the ward. The standard proforma was distributed to the children or caregivers or parents to determine the possible risk factors that might be associated with microsporidiosis. The stool samples were stained with CFW and MGCK staining. The prevalence rate of microsporidiosis in children with malignancies was 77.4% which 82 out of 106 samples were positive of microsporidia spores. Data from the sociodemographic characteristics did not present any significant association with microsporidiosis. Children with hematological cancer were the dominant group with microsporidiosis (64.2%). The clinical manifestations that associated with microsporidiosis were vomiting (χ² value: 8.048, p value: 0.005, OR: 0.290, 95% CI: 0.099-0.851) and stool without mucous (χ² value: 4.138, p value: 0.042, OR: 3.200, 95% CI: 1.002-10.224). Multiple logistic regression analysis showed that children presented with vomiting were 6.564 times more likely to have microsporidiosis compared to those who had not (β=1.182, SE=0.732, Wald χ²=6.614, p value=0.010, OR=6.564, 95% CI=1.565-27.539). The clinical symptoms which occurred in malignancy children were uncertain whether it is caused by microsporidiosis itself or treatment that they encountered with. The environmental risk factors did not contribute to any significant association with microsporidiosis (p value > 0.05). The evaluation of CFW staining performance with the reference standard method which was MGCK staining for detection of microsporidia spore in sample was done. The sensitivity of CFW staining was high (95.5%) but the specificity was very low (4.3%). Hence, it would contribute to a flaw in the identification of microsporidia. As a conclusion, the study gives a baseline data for microsporidia infection in malignancy children in Malaysia. Therefore, the further study is needed in term to develop the better prevention and control against microsporidiosis in malignancy children. Moreover, the corroboration between CFW and MGCK staining methods can be apply in clinical service as a routine screening method for the detection of microsporidia infection in patient samples.